(untitled) (BASASTRA: JURNAL KAJIAN BAHASA DAN SASTRA INDONESIA, 2025)
This research examines the understanding of folklore studies within the framework of Muhammadiyah values using a literature review approach. Through the analysis of ten related articles, this study explores the relationship between folklore and Islamic values, especially in the context of Al-Islam Kemuhammadiyahan Education. The research results highlight the diversity of Muhammadiyah values reflected in folklore, including moral values, faith and religious education. In the context of character education, folklore is identified as an effective means of strengthening the morality and character of individuals and society. In addition, this research shows a positive relationship between Muhammadiyah values and Learning Theory and Character Education, with the application of learning models that support the development of student creativity and involvement. Students’ positive responses to folklore learning show the relevance of this study and strengthening Muhammadiyah values in the educational context. The results of this literature show that folklore is not just entertainment, but also has great potential as a medium for character and moral education that is in line with the values of Al-Islam and Kemuhammadiyahan.